Penyelesaian Kasus Mesum melalui Peradilan Adat Gampong di Aceh (Suatu Kajian Kasus di Banda Aceh) - Teuku Muttaqin Mansur (Sharia and Law Faculty, 2012)
Treatment nasty case in Banda Aceh, Aceh province could also be implemented through Local Customary Courts. Settlement through customary courts always be informal or through peace way. On the other hand, Aceh Qanun No. 14 of nasty arranges it as well, in which the nasty cases will be resolved by the Syar’iyah Court. This study aimed to see, if the Local Customary Court has the authority to deal with nasty case, and whether the decision made by the Local Customary Court shall be final and tight. The study was conducted by interviewing Local Customary Court judges, Wilayatul Hisbah and Communities. The method used was a qualitative study. The result showed that both the Local Customary Courts and the Syar‘iyah Court have the same authority in handling the nasty case in Banda Aceh. In fact, sometimes, the local customary courts also resolve cases that have been categorized as adultery. Treatment cases of nasty, with local customary court have no final and strong legal force, because if the parties are not satisfied with the decision of the Customary Court, they can still bring the Government of Aceh in order to perform an amendment to the articles of those Qanun. Then, the special cases that are categorized as adultery should immediately be resolved by the Syar’iyah Court.